(untitled) (Council for Agricultural Science and Technology (CAST), 2003)
New Special Publication. This new publication compiles national, state, and territory winning entries from an essay contest for students in 6th, 7th, and 8th grades. The contest was conducted by CAST, with support from the U.S. Department of Agriculture’s™ Cooperative State Research, Education, and Extension Service and other sponsors. Students wrote essays on one of seven preselected topics dealing with agricultural science. More than 800 entries were received from 40 states, the District of Columbia, and the U.S. Virgin Islands. Entries were judged on originality, creativity, organization, background research, and writing mechanics. Winners were selected at the School, Congressional District, and National levels. District and state winners were invited to attend special VIP Day celebrations, hosted by participating universities nationwide. Three national winners were chosen and awarded a trip to Washington, D.C. during National Agriculture Week (March 21, 2003).